DINAMIKA PEMEROLEHAN SINTAKSIS DAN METAFUNGSI BAHASA PADA ANAK USIA LIMA TAHUN: ANALISIS MIXED METHODS DAN FUNCTIONAL GRAMMAR - azzahroh, jauzaa syariifah; ulya, Ridha hasnul; eryanti, Boty; amelia, Dhita; afrianika, Dila; putri, Enjelly maysi; alia, Juwita; Nur, Lupia ainia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to classify syntactic patterns and communicative functions in the first language acquisition of a five-year-old child. The method employed is a mixed methods design with naturalistic observation conducted over one month. Spontaneous speech data were collected using the participant observation technique (simak libat cakap), validated through expert triangulation, and analyzed quantitatively based on the frequency of sentence patterns and Mean Length of Utterance (MLU), as well as qualitatively using the Systemic Functional Grammar approach. The results indicate a dominance of S-P-O structures (32.3%) and S-P (29.9%), with an MLU ranging from 4.50 to 4.90 morphemes, confirming a stable transition from the telegraphic stage to more complex grammar. Functional analysis reveals that the child’s structural choices are simultaneously governed by ideational, interpersonal, and textual metafunctions, realized through subordinating conjunctions, politeness modulation, and discourse cohesion, although still accompanied by the omission of contextual elements and interference from regional phatic particles. The conclusion emphasizes that syntactic acquisition at this age is adaptive, multidimensional, and grounded in usage-based principles. The practical implication recommends the integration of functional-pragmatic indicators into early linguistic assessment, as well as the design of early childhood education (PAUD) curricula that utilize multilingual variation as a cognitive asset for children.